Games e terceira idade: um estudo de caso com o wii sports - Quintana, Guilherme Henrique (2011)
Currently the focus of the market for digital games is the development of games for the general public, and especially for the juvenile segment. Moreover, there is the growing number of elderly people on the planet. Thus, this research aims to outline the central features of today's games from the interaction with the elderly population using the Nintendo Wii. The secondary objectives are to create interactions with Wii workshops for seniors; observe interactions, collect data, analyze the data and, finally, point of game design elements that may harm or help the elderly in four areas: visual, sound, interactivity and sociability. The research involved different strategies and methods: encounters with the elderly group, workshops, practical activities with the Wii, asking questions, reading of texts on the elderly and game design, review and reformulation of the initial questions and the development of the dissertation. Data collection was conducted through questionnaires prepared by the researcher, video recordings, photographs and data from the video game software through the use of games in the collection Wii Sports, which include five sports: tennis, boxing, bowling, baseball and golf in weekly meetings during two months with the group of participants in the volleyball team "Golden Age" of Itatiba / SP, composed of elderly. To analyze the data collected, authors were used in areas that include psychology in the elderly (Argimon), caloric expenditure with the use of games similar to those used in this study (Robin R. Mellecker and Alison M. McManus), cognitive effects in elderly users of games, the market revolution promoted by the Wii, game development, the possible insertion of the elderly population in this market and the tools used in creating these works (Nelson Zagalo and Rui Prada). In the field of critical studies about games, were fundamental to the research Jesus de Paula Assis, Roger Tavares, Vinicius Mano, Edson P. Pfutzenreuter, Andrés Rollings, Ernest Adams, Celia Pearce, among others. The results highlighted the need for the reformulation of the game design aimed at the elderly as this segment of the population has physical and behavioral characteristics significantly different from the adult audience and / or juvenile. Aspects such as the choice of colors and arrangement of information on the screen, the sound frequencies used, methods of handling the interaction and preference for more cooperative than competitive games stood out as key factors to please and meet the needs of this growing audience in our society